A Comparison of the Likelihood Ratio Test and the Variance‐Stabilising Transformation‐Based Tests for Detecting Association of Rare Variants. (14th March 2013) - Xing, Guan; Ku, Hung‐Chih; Xing, Chao
Summary: In a recent paper in this journal, the use of variance‐stabilising transformation techniques was proposed to overcome the problem of inadequacy in normality approximation when testing association for a low‐frequency variant in a case‐control study. It was shown that tests based on the variance‐stabilising transformations are more powerful than Fisher's exact test while controlling for type I error rate. Earlier in the journal, another study had shown that the likelihood ratio test (LRT) is superior to Fisher's exact test, Wald's test, and Pearson's χ 2 test in testing association for low‐frequency variants. Thus, it is of interest to make a direct comparison between the LRT and the tests based on the variance‐stabilising transformations. In this commentary, we show that the LRT and the variance‐stabilising transformation‐based tests have comparable power greater than Fisher's exact test, Wald's test, and Pearson's χ 2 test.